Ceftriaxone compared with benzylpenicillin in the treatment of neurosyphilis in France: a retrospective multicentre study. Issue 10 (October 2021) - Bettuzzi, Thomas; Jourdes, Aurélie; Robineau, Olivier; Alcaraz, Isabelle; Manda, Victoria; Molina, Jean Michel; Mehlen, Maxime; Cazanave, Charles; Tattevin, Pierre; Mensi, Sami; Terrier, Benjamin; Régent, Alexis; et al.
Summary: Background: Intravenous benzylpenicillin is the gold-standard treatment for neurosyphilis, but it requires prolonged hospitalisation. Ceftriaxone is a possible alternative treatment, the effectiveness of which remains unclear. We aimed to assess the effectiveness of ceftriaxone compared with benzylpenicillin in the treatment of neurosyphilis. Methods: We did a retrospective multicentre study including patients with neurosyphilis who were treated at one of eight tertiary care centres in France, from Jan 1, 1997, to Dec 31, 2017. We defined neurosyphilis as positive treponemal and non-treponemal tests and at least one of otic syphilis, ocular syphilis, either neurological symptom with a positive result on cerebrospinal fluid (CSF)-VDRL or CSF-PCR tests, or more than five leukocytes in a CSF cell count. Patients with neurosyphilis were identified from the medical information department database of each centre and assigned to one of two groups on the basis of the initial treatment received (ie, benzylpenicillin group or ceftriaxone group). The primary outcome was the overall clinical response (ie, proportion of patients with a complete or partial response) 1 month after treatment initiation. The secondary endpoints were proportions of patients with a complete response at 1 month and serological response at 6 months, and length of hospital stay. Findings: Of 365 patients with a coded diagnosis of neurosyphilis in one of the eight care centres during 1997–2017, 208 were included in this study (42 in the ceftriaxone group and 166 in the benzylpenicillin group). The mean age of patients was 44·4 years (SD 13·4), and 193 (93%) were men. We observed 41 instances of overall clinical response (98%) in the ceftriaxone group versus 125 (76%) in the benzylpenicillin group (crude odds ratio [OR] 13·02 [95% CI 1·73–97·66], p=0·017). After propensity score weighting, overall clinical response rates remained different between the groups (OR 1·22 [95% CI 1·12–1·33], p<0·0001). 22 (52%) patients in the ceftriaxone group and 55 (33%) in the benzylpenicillin group had a complete response (crude OR 2·26 [95% CI 1·12–4·41], p=0·031), with no significant difference after propensity score weighting (OR 1·08 [95% CI 0·94–1·24], p=0·269). Serological response at 6 months did not differ between the groups (21 [88%] of 24 in the ceftriaxone group vs 76 [82%] of 93 in the benzylpenicillin group; crude OR 1·56 [95% CI 0·42–5·86], p=0·50), whereas hospital stay was shorter for patients in the ceftriaxone group than for those in the benzylpenicillin group (mean 13·8 days [95% CI 12·8–14·8] vs 8·9 days [5·7–12·0], p<0·0001). No major adverse effects were reported in either group. Interpretation: Our results suggest that ceftriaxone is similarly effective to benzylpenicillin for the treatment of neurosyphilis, potentially decreasing the length of hospital stay. Randomised, controlled trials should be done to confirm these results. Funding: None.